If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16x + -6 = 4 + 19x Reorder the terms: -6 + 16x = 4 + 19x Solving -6 + 16x = 4 + 19x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-19x' to each side of the equation. -6 + 16x + -19x = 4 + 19x + -19x Combine like terms: 16x + -19x = -3x -6 + -3x = 4 + 19x + -19x Combine like terms: 19x + -19x = 0 -6 + -3x = 4 + 0 -6 + -3x = 4 Add '6' to each side of the equation. -6 + 6 + -3x = 4 + 6 Combine like terms: -6 + 6 = 0 0 + -3x = 4 + 6 -3x = 4 + 6 Combine like terms: 4 + 6 = 10 -3x = 10 Divide each side by '-3'. x = -3.333333333 Simplifying x = -3.333333333
| x-2x+8/3=1/4(x-2-x/6)-3 | | 8(v+1)=2v+38 | | 16x-6+4+19x=90 | | 45=5(3x-2) | | 1=2-S | | y=x^2-8x+11 | | 2x-4+x=41 | | 25x+7-27x=3-6 | | 16x-6+4+19x=180 | | 2x-4(-4x-2)=152 | | y-11=x(x-8) | | 11+x=6(5x-3) | | 132+77t= | | -w^6+4w^4-4w^2+1=3.981 | | 60-24x= | | -3-3n=-3(2n-5) | | -15=r/5 | | -3z=8-3z | | 24x+64= | | Y=-4x^2+16x+20 | | 3a^3+3ab^2+2a^2b+2b^3= | | -(5-2)=5+2 | | 5x/8-3x/8 | | x*x-2x=3x+108 | | 5/6(-3/4) | | -42+-54= | | Y=-4x^2+16+20 | | 2x^4-x^3-6x^2=0 | | 4z+3z+6=90 | | 100-50d= | | x/y-1/5 | | x^2-2(x-1)=x^2(x-1) |